(untitled) (American Journal of Islam and Society, 2014)
During the 2007 provincial election campaign, Conservative party candidate John Tory proposed extending government funding to all faith-based schools in Ontario. This was met with strong public and media opposition due to fears of radicalization and indoctrinating students in religious beliefs considered outdated and a threat to Canadian norms (particularly with Islamic schools). It is with this anecdote that editors Graham P. McDonough, Nadeem Memon, and Avi L. Mintz introduce Discipline, Devotion, and Dissent: Jewish, Catholic, and Islamic Schooling in Canada. As they note, the impassioned debate surrounding Tory’s election promise, as well as his ensuing loss, indicate that religious education is a particularly contentious topic in an increasingly secular society. And yet there is surprisingly little scholarly literature on this topic. The editors seek to address this gap through this excellent and much needed contribution to the field. Focusing solely on Catholic, Islamic, and Jewish schools, which make up the vast majority of Canada’s full-time religious schools, the editors seek not to provide an overview of religious education, but to address three issues: The schools’ aims and practices, how they “negotiate the tension between the demands of the faith and the expectation that they educate Canadian citizens,” and how they “respond to internal dissent.” ...